Detection of multidrug-resistant Klebsiella pneumoniae in chicken samples collected from wet markets of Dhaka City - Turna, Adrita Saha; Hussain, Ashraful (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.